The art of mixing a visual guide to recording, engineering, and production - Gibson, David 1957-; Petersen, George; Gale Group (Boston, Mass. Thomson Course Technology PTR/ArtistPro Pub., 2005)
A revised full-color edition with even more examples of musical styles visually illustrated to reveal how sound "looks" in a professionally mixed song. This volume provides insight into how sound works in a three-dimensional field, helping the reader understand how to apply mixing techniques to their own recordings.
Introduction -- The best of the color visuals -- Chapter 1. All aspects of a recorded piece of music -- Chapter 2. Visual representations of "imaging" -- Chapter 3. Guides to a great mix (reasons for creating one style of mix or another) -- Chapter 4. Functions of studio equipment and visual representations of all parameters -- Chapter 5. Musical dynamics created with studio equipment -- Chapter 6. Styles of mixes -- Chapter 7. Magic in music, songs, and equipment -- Chapter 8. 3D sound processors and surround sound mixing -- Chapter 9. Mixing procedures -- Appendix A - D -- Index.
Electronic reproduction.
Keywords: Sound -- Recording and reproducing; Sound recordings -- Production and direction; Electronic books